Challenges facing the adoption of Electronic Fiscal Devices (EFDs) in revenue collection: A case of Morogoro Municipality, Tanzania - Cornel, Delphine (Mzumbe University, 2024)
Description: Dissertation Submitted to the School of Business in Partial fulfillment of the Requirements for the Award of Master of Business Administration (MBA) of Mzumbe University